A key role for the novel coronary artery disease gene JCAD in atherosclerosis via shear stress mechanotransduction. Issue 11 (4th October 2019) - Douglas, Gillian; Mehta, Vedanta; Al Haj Zen, Ayman; Akoumianakis, Ioannis; Goel, Anuj; Rashbrook, Victoria S; Trelfa, Lucy; Donovan, Lucy; Drydale, Edward; Chuaiphichai, Surawee; Antoniades, Charalambos; Watkins, Hugh; et al.
Abstract: Aims: Genome-wide association studies (GWAS) have consistently identified an association between coronary artery disease (CAD) and a locus on chromosome 10 containing a single gene, JCAD (formerly KIAA1462 ). However, little is known about the mechanism by which JCAD could influence the development of atherosclerosis. Methods and results: Vascular function was quantified in subjects with CAD by flow-mediated dilatation (FMD) and vasorelaxation responses in isolated blood vessel segments. The JCAD risk allele identified by GWAS was associated with reduced FMD and reduced endothelial-dependent relaxations. To study the impact of loss of Jcad on atherosclerosis, Jcad −/− mice were crossed to an ApoE −/− background and fed a high-fat diet from 6 to16 weeks of age. Loss of Jcad did not affect blood pressure or heart rate. However, Jcad −/− ApoE −/− mice developed significantly less atherosclerosis in the aortic root and the inner curvature of the aortic arch. En face analysis revealed a striking reduction in pro-inflammatory adhesion molecules at sites of disturbed flow on the endothelial cell layer of Jcad −/− mice. Loss of Jcad lead to a reduced recovery perfusion in response to hind limb ischaemia, a model of altered in vivo flow. Knock down of JCAD using siRNA in primary human aortic endothelial cells significantly reduced the response to acute onset of flow, as evidenced by reduced phosphorylation of NF-КB, eNOS, and Akt. Conclusion: The novel CAD gene JCAD promotes atherosclerotic plaque formation via a role in the endothelial cell shear stress mechanotransduction pathway.